"But it feels swollen!": the frequency and clinical characteristics of people with knee osteoarthritis who report subjective knee swelling in the absence of objective swelling. (8th November 2021) - Tanaka, So; Nishigami, Tomohiko; Ohishi, Koji; Nishikawa, Kazutaka; Wand, Benedict M.; Stanton, Tasha R.; Yamashita, Hirofumi; Mibu, Akira; Tokunaga, Masami; Yoshimoto, Takaaki; Ushida, Takahiro
Abstract : Supplemental Digital Content is Available in the Text. The present results support the coexistence of altered body image (subjective without objective swelling) and pain, disability, and maladaptive beliefs in people with knee osteoarthritis. Abstract: Introduction: There are complex interactions between pain and perceptions of the painful body part in musculoskeletal disorders, and disruption of various body representations in people with chronic pain. Objectives: The purpose of this study was to investigate how frequently people with knee osteoarthritis (OA) complain of swelling without objective evidence of swelling, and describe the clinical characteristics of this population. Methods: Forty-six people with knee OA (68.1 ± 8.8 years) participated in this cross-sectional study. Subjective and objective swelling was evaluated by knee-specific body perception questionnaire and ultrasonography, respectively. Pain intensity, disability, pain-related beliefs, 2-point discrimination threshold, and quadriceps muscle strength were also evaluated. Results: Approximately 1/3 of participants (n = 15) had subjective feelings of knee swelling in the absence of objective swelling (S only). Fifteen participants had both subjective and objective knee swelling (S + O group) and 16 had neither subjective nor objective knee swelling (No S/O group). Participants in the S only group had similar pain or disability as those in the S + O group but had more severe pain or disability than those with in the No S/O group. Those in the S only group also had larger 2-point discrimination distance threshold at the medial knee (impaired tactile acuity) than those in the S + O group and had more dysfunctional pain catastrophizing and pain-related self-efficacy than both other groups. Conclusion: Our results suggest that about 30% of people with knee OA perceive swelling of the knee in the absence of any objective swelling and that this is accompanied by severe pain and functional disability. Considering altered body image of the knee may reveal relevant treatment-based subgroups in people with knee OA.